Unusual Quasi 10‐Day Planetary Wave Activity and the Ionospheric Response During the 2019 Southern Hemisphere Sudden Stratospheric Warming. Issue 6 (10th June 2021) - Wang, J. C.; Palo, S. E.; Forbes, J. M.; Marino, J.; Moffat‐Griffin, T.; Mitchell, N. J.
Abstract: An unusual sudden stratospheric warming (SSW) event occurred in the Southern Hemisphere in September 2019. Ground‐based and satellite observations show the presence of transient eastward‐ and westward‐propagating quasi‐10 day planetary waves (Q10DWs) during the SSW. The planetary wave activity maximizes in the mesosphere and lower thermosphere region approximately 10 days after the SSW onset. Analysis indicates that the westward‐propagating Q10DW with zonal wave number s = 1 is mainly symmetric about the equator, which is contrary to theory which predicts the presence of an antisymmetric normal mode for such planetary wave. Observations from microwave limb sounder and sounding of the atmosphere using broadband emission radiometry are combined with meteor radar wind measurements from Antarctica, providing a comprehensive view of Q10DW wave activity in the Southern Hemisphere during this SSW. Analysis suggests that the Q10DWs of various wavenumbers are potentially excited from nonlinear wave‐wave interactions that also involve stationary planetary waves with s = 1 and s = 2. The Q10DWs are also found to couple the ionosphere with the neutral atmosphere. The timing of the quasi‐10‐day oscillations (Q10DOs) in the ionosphere are contemporaneous with the Q10DWs in the neutral atmosphere during a period of relatively low solar and geomagnetic activity, suggesting that the Q10DWs play a key role in driving the ionospheric Q10DOs during the Southern SSW event. This study provides observational evidence for coupling between the neutral atmosphere and ionosphere through the upward propagation of global scale planetary waves. Plain Language Summary: Sudden stratospheric warmings (SSWs) are a common dynamical feature in the Northern Hemisphere, but they rarely happen in the Southern Hemisphere because of weaker planetary wave activity due to smaller land/sea thermal differences. In September 2019, a record‐strong SSW was observed in the Southern Hemisphere, accompanied by the amplification of traveling planetary waves with a period near 10 days during the onset of this Southern Hemisphere SSW. Analysis suggests that the quasi 10‐day planetary waves can drive the quasi‐10‐day oscillations in the ionosphere. Our result suggests the amplification of the quasi 10‐day planetary waves during SSWs can make significant impacts on the upper atmosphere. Key Points: S0 and W1 quasi‐10 day planetary waves (Q10DWs) were forced during the 2019 Southern sudden stratospheric warming (SSW), possibly through Q10DW‐E1 nonlinear interactions with stationary planetary waves Latitudinal structures of stratospheric Q10DWs are similar to those expected based on solutions to Laplace's tidal equation The Q10DWs couple the neutral atmosphere and ionosphere during the 2019 Antarctica SSW